A study on the performance of the regulatory functions of the Kapisanan ng mga Brodkaster sa Pilipinas, Iloilo Chapter. - Advincula, Rebecca
Generally, regulations are viewed as important factors in the functions of an industry or organization. Like any other industry, broadcasting needs to be regulated. The Kapisanan ng mga Brodkaster sa Pilipinas is a self-regulatory body which implements regulations affecting the programming operations of the broadcast stations. However, not all regulations are said to be followed by the situations. It is in this regard that this study was conducted. Three factors were considered in finding out whether KBP regulations are important to the operations of the stations: the importance and necessity of these regulations; the capability of the KBP in implementing these regulations; and the extent of public participation between KBP and its member stations. The necessity level was activities covered by these regulations, and the relative need of the stations to these regulations. The capability level was determined by a study on the frequent observance of the stations to the regulations, the objectives of the respondent stations and the major output, organizational structure, and budget of the KBP as a regulatory body. Public participation was determined by a study of the frequency used modes of interaction involved in the implementation of the regulations, the problem met in the process, and the respondent stations? rating/assessment of the KBP. The study made use of the one-shot survey design with interview schedule and use of questionnaire as main instruments. The respondents for the KBP are the stations managers while respondents for the regulated are the production staff of the local stations. A total of twelve stations were taken as respondents for the study. Results showed too many regulations are imposed by the KBP and are not strictly followed by the stations. Regulations that are mostly followed are those which pertain to public commentaries and issues, the presentation of materials regarding sex and violence and the airing of commercials. Results showed that these regulations are necessary to maintain a certain level of excellence and professionalism in the broadcast industry. Likewise, the KBP is capable of implementing regulations to the stations as shown by the constant interaction between the regulator and the regulated.